The needed link between open science and science diplomacy—A Latin American perspective - Camacho Toro, Reina; Cumba Garcia, Luz M.; Galvis, Laura A.; Echeverría-King, Luisa F.; Pantović, Branislav; Alarcón-López, Claudia; Suarez, Verónica Rossana; Figueroa, Pedro; Torres-Atencio, Ivonne; Widmaier, Claudia; Fraga, Tatiana Rodrigues; Benavides, Susan (Frontiers in Research Metrics and Analytics, 2024)
The relevance of science diplomacy and open science in today's world is undeniable. Science diplomacy enables countries to jointly address pressing global challenges, such as climate change, pandemics, and food security. Open science, promoting accessible and transparent research, plays a pivotal role in this context. Nevertheless, the degree of openness is subject to specific circumstances, contingent upon varying factors, including local knowledge and resources. Latin America has not only been at the forefront of pioneering open access strategies, making it an interesting case to study, but it has also shown a tangible interest in using science diplomacy. Our research employs a mixed-methods approach, incorporating a quantitative survey involving 50 organizations and initiatives dedicated to promoting open science in Latin America, along with two qualitative focus group studies. Our primary objective is to assess if and how these entities use science diplomacy to achieve their objectives. Non-policy entities were prioritized due to their institutional stability in the region. We highlight successful strategies and delve into the existing barriers hindering the full implementation of open science principles. Our research aims to enhance collaboration between these organizations and policy and decision-makers by providing a set of recommendations in that direction. By shedding light on the current landscape and dynamics of open science in Latin America, we aspire to focus on science diplomacy, facilitate informed decision-making, and formulate policies that further propel the region along the path of openness, collaboration, and innovation in scientific research.